Healthcare Quality and HIT - International Standards, China Practices, 1st edition - Liu, Jilan (Routledge, 2020)
How Chinese hospitals have been growing and adopting international standards such as JCI and HIMSS EMRAM to fuel their advancements is not well-known to the western world. In this book, Jilan Liu, as former Principal Consultant of JCI and current Chief Executive Officer for HIMSS Greater China, presents a selection of case examples written by Chinese hospital executives and staff showcasing first-hand experiences and insights into how the leading healthcare organizations grow and continue their success in China.